Silicon‐mediated changes in polyamines participate in silicon‐induced salt tolerance in Sorghum bicolor L. (17th April 2015) - Yin, Lina; Wang, Shiwen; Tanaka, Kiyoshi; Fujihara, Shinsuke; Itai, Akihiro; Den, Xiping; Zhang, Suiqi
Abstract: Silicon (Si) is generally considered a beneficial element for the growth of higher plants, especially under stress conditions, but the mechanisms remain unclear. Here, we tested the hypothesis that Si improves salt tolerance through mediating important metabolism processes rather than acting as a mere mechanical barrier. Seedlings of sorghum ( S orghum bicolor L.) growing in hydroponic culture were treated with NaCl (100 mm ) combined with or without Si (0.83 mm ). The result showed that supplemental Si enhanced sorghum salt tolerance by decreasing Na + accumulation. Simultaneously, polyamine (PA) levels were increased and ethylene precursor (1‐aminocyclopropane‐1‐carboxylic acid: ACC) concentrations were decreased. Several key PA synthesis genes were up‐regulated by Si under salt stress. To further confirm the role of PA in Si‐mediated salt tolerance, seedlings were exposed to spermidine (Spd) or a PA synthesis inhibitor (dicyclohexylammonium sulphate, DCHA) combined with salt and Si. Exogenous Spd showed similar effects as Si under salt stress whereas exogenous DCHA eliminated Si‐enhanced salt tolerance and the beneficial effect of Si in decreasing Na + accumulation. These results indicate that PAs and ACC are involved in Si‐induced salt tolerance in sorghum and provide evidence that Si plays an active role in mediating salt tolerance. Abstract : This study demonstrates that silicon improves salt tolerance through regulating polyamines (PAs) and ethylene levels in sorghum. The high levels of PAs maintain K + /Na + homeostasis and moderate salt‐induced senescence, leading to improved salt tolerance. These results support the idea that silicon is involved in mediating the salt tolerance response in plants.